2016
DOI: 10.1021/acsami.6b12683
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processable Ionic Liquid as an Independent or Modifying Electron Transport Layer for High-Efficiency Perovskite Solar Cells

Abstract: Inorganic metal oxide, especially TiO, has been commonly used as an electron transport layer (ETL) in regular-structure (n-i-p) planar heterojunction perovskite solar cells (PHJ-PSCs) but generally suffers from high electron recombination rate and incompatibility with low-temperature solution processability. Herein, by applying an ionic liquid (IL, 1-ethyl-3-methylimidazolium hexafluorophosphate ([EMIM]PF)) as either a TiO-modifying interlayer or an independent ETL, we investigated systematically IL interface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 64 publications
4
94
0
1
Order By: Relevance
“…The steady‐state photoluminescence (PL) spectra were collected to investigate exciton separation. As shown in Figure a, the spectra show peaks at approximately 770 nm, which is in agreement with the PL spectrum of MAPbI 3 . For the absorber layer MAPbI 3 , the PL intensity of the dual‐effect devices was quenched with an increasing DMSO concentration from 1.0 to 2.0 μL mL −1 , indicating efficient exciton separation in the MAPbI 3 layer.…”
Section: Resultssupporting
confidence: 80%
“…The steady‐state photoluminescence (PL) spectra were collected to investigate exciton separation. As shown in Figure a, the spectra show peaks at approximately 770 nm, which is in agreement with the PL spectrum of MAPbI 3 . For the absorber layer MAPbI 3 , the PL intensity of the dual‐effect devices was quenched with an increasing DMSO concentration from 1.0 to 2.0 μL mL −1 , indicating efficient exciton separation in the MAPbI 3 layer.…”
Section: Resultssupporting
confidence: 80%
“…[14,40,41] However, several studies have shown that due to improved energy alignment and reduced interfacial recombination, SnO 2 is a superior choice of ETL in planar heterojunction perovskite solar cells, resulting in reduced hysteresis and better device performance. [14,40,41] However, several studies have shown that due to improved energy alignment and reduced interfacial recombination, SnO 2 is a superior choice of ETL in planar heterojunction perovskite solar cells, resulting in reduced hysteresis and better device performance.…”
Section: Resultsmentioning
confidence: 99%
“…[28,36,37] Ionic liquids (ILs) have been reported to improve the per formance of perovskite solar cells and have been used both as an additive to the perovskite precursor solution, where it is employed to tune crystallization kinetics of the perovskite film, [38,39] and as an interlayer between TiO 2 and the perovskite material. [41] There, the authors also show that although the best performance is achieved when a double layer of TiO 2 /IL is used, a respectable performance can be achieved simply by treating the surface of the electrode (in this case fluorinedoped tin oxide (FTO)) with the IL. [40] In that work, it was shown that treating the TiO 2 surface with BMIMBF 4 results in more efficient electron extraction, which is attributed to a decrease in the work function of the TiO 2 which improves its energy level alignment with the perovskite as well as an increase in electron mobility of the titania due to the pas sivation of trap states on the TiO 2 surface.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a triple‐cation, cesium‐based perovskite structure resulted in a more UV and thermally stable perovskite‐based solar cell . Fluorinated salts have also been shown to increase the stability of perovskite‐based devices due to their hydrophobic properties . For example, incorporation of a multifunctional fluorous‐based photopolymer on the front of the device improves stability as well as the photovoltaic performance .…”
Section: Introductionmentioning
confidence: 99%